SAT0385 CAN MISCLASSIFICATION BETWEEN SPONDYLOARTHRITIS (SPA) AND RHEUMATOID ARTHRITIS (RA) OCCUR? SPA-RELATED CLINICAL MANIFESTATIONS AMONG RA AND SPA PATIENTS - A SYSTEMATIC LITERATURE REVIEW. (2nd June 2020) - Mease, P. J.; Bhutani, M. K.; Hur, P.; Yi, E.; Kim, N.
Abstract : Background: Delayed diagnosis is associated with worse outcomes and poor treatment responses in patients with SpA, including psoriatic arthritis (PsA) and axial spondyloarthritis. 1 Misclassification may be associated with this delay, as SpA and RA, especially seronegative RA, may present with similar manifestations such as joint pain, swelling, fatigue, and disability. Key features that typically distinguish SpA from RA include spine pain, dactylitis, enthesitis, psoriasis, and nail psoriasis. 2 Increased physician awareness of the potential overlap and distinctions between SpA and RA manifestations is needed for the early diagnosis and appropriate treatment for SpA. Objectives: To identify and summarise the published literature on the prevalence of SpA-related clinical manifestations among patients with RA and SpA. Methods: Publications were retrieved from Embase®, Cochrane, MEDLINE®, and MEDLINE® In-Process databases. Studies were included if they were non-interventional, recruited patients with RA and SpA, or patients with seronegative/seropositive RA, and reported the following manifestations: enthesitis, dactylitis, axial symptoms, psoriasis, or nail psoriasis. Two reviewers assessed each citation against predefined eligibility criteria, with discrepancies reconciled by a third independent reviewer. Results: Of the 4479 publications retrieved, 18 studies were included (Figure 1 ). All studies compared SpA populations to patients with RA. Of the 18 studies, 11 studies reported patients with only PsA, 2 studies reported patients with only ankylosing spondylitis (AS), and 5 studies reported mixed SpA populations. Three studies each reported data pertaining to seropositive/seronegative RA and early RA, defined as symptom onset <1 year. The majority (N=12) of studies used ultrasound imaging to identify manifestations of interest. Enthesitis (N=17) was the most frequently evaluated manifestation while axial symptoms (N=2) was least evaluated. Of the studies reporting enthesitis, the majority (N=14) reported a higher prevalence of enthesitis in the SpA cohort compared to the RA cohort. The remaining studies (N=3) reported no significant difference in enthesitis between the SpA and RA cohorts. Notably, these 3 studies comprised of the 2 studies evaluating only AS patients, and all 3 studies evaluated late RA patients. In contrast, the 3 studies that reported early RA and PsA patients found a significantly higher prevalence of enthesitis in early PsA vs. early RA cohort. Two of the 3 studies reporting RA serostatus found a higher prevalence of enthesitis, psoriasis, and/or nail psoriasis in the SpA population compared to seronegative and seropositive RA cohorts. All studies reporting axial symptoms, dactylitis, psoriasis, and nail psoriasis found a higher prevalence of the corresponding manifestation in the SpA vs. RA cohort. Conclusion: While this review found a higher prevalence of key SpA-related clinical manifestations in SpA vs. RA, overlap was present suggesting that misclassification could occur. Differences in the prevalence of manifestations were also seen in the early vs. late RA populations as well as by RA serostatus. This suggests that an earlier and comprehensive evaluation, including advanced imaging of peripheral manifestations such as enthesitis, dactylitis, axial symptoms, and skin signs such as psoriasis and nail disease, among RA and SpA patients may reduce misclassification and inappropriate treatment. Further research is needed to confirm these findings. References: [1]Seo et al. Clin Rheumatol. 2015;34:1397-1405. [2]Merola et al. RMD. 2018;4:e000656. Acknowledgments: This study was sponsored by Novartis Pharmaceuticals Corporation, East Hanover, NJ. Disclosure of Interests: Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Mohit Kumar Bhutani Employee of: Novartis Healthcare Pvt Ltd, Peter Hur Employee of: Novartis Pharmaceuticals Corporation, Esther Yi Employee of: Novartis Pharmaceuticals Corporation, Nina Kim Employee of: Postdoctoral fellow at the University of Texas at Austin and Baylor Scott and White Health, providing services to Novartis Pharmaceuticals Corporation